2014
DOI: 10.1093/jxb/eru075
|View full text |Cite
|
Sign up to set email alerts
|

Investigating water transport through the xylem network in vascular plants

Abstract: Our understanding of physical and physiological mechanisms depends on the development of advanced technologies and tools to prove or re-evaluate established theories, and test new hypotheses. Water flow in land plants is a fascinating phenomenon, a vital component of the water cycle, and essential for life on Earth. The cohesion-tension theory (CTT), formulated more than a century ago and based on the physical properties of water, laid the foundation for our understanding of water transport in vascular plants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 114 publications
2
73
1
1
Order By: Relevance
“…8, D-F). Vascular bundles and conduits are necessary for water transport (Kim et al, 2014). Moreover, the water potential values were all higher in es1-1 than in the wild type in various tissues, including roots, stems, leaves, and sheath, which indicated that the ability to transport water was stronger in es1-1 than in the wild type ( Fig.…”
Section: Es1 Affects the Density Of Leaf Stomata In Ricementioning
confidence: 90%
See 1 more Smart Citation
“…8, D-F). Vascular bundles and conduits are necessary for water transport (Kim et al, 2014). Moreover, the water potential values were all higher in es1-1 than in the wild type in various tissues, including roots, stems, leaves, and sheath, which indicated that the ability to transport water was stronger in es1-1 than in the wild type ( Fig.…”
Section: Es1 Affects the Density Of Leaf Stomata In Ricementioning
confidence: 90%
“…This, in turn, accelerates water circulation in the plant, thus leading to predicted in situ enrichment of metal ions cotransported with water (Kim et al, 2014). To test this hypothesis in this mutant, we determined the mineral concentrations of different tissues of es1-1 and wild-type plants at the mature stage.…”
Section: Es1 Affects the Density Of Leaf Stomata In Ricementioning
confidence: 99%
“…For the dry period from 2 June to 24 June soil moisture changes above the ZFP were balanced according to Equation (1). Although the ZFP was located within the root zone it can be assumed that soil moisture changes below the ZFP were mainly due to the downward movement of water and only to a minor extent because of root water extraction.…”
Section: Diurnal Cycle Of Transpiration Estimated Using Granier's Orimentioning
confidence: 99%
“…Such estimates are usually obtained by measuring the speed of xylem sap movement through the stem using heat sensors. Three different systems of heat sensors are commonly used [1]: (i) heat pulse velocity sensors; (ii) heat field deformation sensors; and (iii) thermal dissipation sensors. Vandegehuchte and Steppe [2] discussed the working principles and applicability of these sensors in detail, which we will not include in this work.…”
Section: Introductionmentioning
confidence: 99%
“…12C). Since vessel diameter is positively correlated with the volume of water transported and inversely correlated with the safety (lower risk of cavitation) of the conductive system (Carlquist, 1980;Vaselatti et al, 2001;Kim et al, 2014) it seems that this species did not show plasticity to change vessel diameter probably associated with lower hydraulic security in comparison to waterlogged plants. It is also important to highlight that values of wholeplant hydraulic conductance (K T ) were similar to those of droughted plants (Fig.…”
Section: Chapter 1)mentioning
confidence: 99%